Constructivism in Arabic Language Pedagogy: An Exploration Through Islamic Higher Education Settings - Haerullah, Ira Safira; Muhammad Jundi; Hasibuan, Renni; Ranita Sari; Desi Asmarita (ELOQUENCE : Journal of Foreign Language, 2024)
Background: Numerous studies have delved into the constructivist paradigm in the context of language learning. However, exploration of its application in Arabic language instruction, particularly within higher education settings, remains an intriguing area for further investigation. Purpose: This research aims to conduct a thorough analysis of the implementation of Constructivist Theory in Arabic Language Education within Islamic Higher Education Institutions, through a review of relevant previous studies. Method: The research methodology employed is a qualitative approach with a Literature Review design, utilizing documentation as the primary data collection method, subsequently analyzed using content analysis and interactive analysis techniques. Results and Discussion: Findings reveal that the application of constructivist-based instructional models in Arabic language education at the higher education level significantly contributes to enhancing the quality of the learning process and outcomes. The development of instructional materials based on constructivism also yields significant positive impacts, enhancing students' Arabic language proficiency and fostering more meaningful learning experiences. Conclusions and Implications: The conclusions affirm that the constructivist approach is effective in enhancing Arabic language education in the academic environment of higher education, particularly within the context of Arabic language education.